Obstacles to Implementation of Differentiation Learning in Sociology Subjects - A. Octamaya Tenri Awaru,; M. Ridwan Said Ahmad,; Andi Sadriani, (Technium Social Sciences Journal, 2023)
The implementation of the Merdeka curriculum at SMA Makassar City poses a significant challenge for sociology teachers in implementing differentiated learning. This type of qualitative research with a case study approach was used in this study which focused on the phase of teacher adaptation to an independent curriculum. Teachers from various backgrounds from both public and private schools were the main informants in this study. Data were collected through in-depth interviews, and observations made during the differentiated learning process were applied by teachers. The data obtained is then analyzed through three stages., Validation through source triangulation. The results of the study found that there are at least four main obstacles faced by teachers in their efforts to implement differentiated learning. First, the complexity of the process in differentiated learning causes some teachers to feel overwhelmed in designing and managing learning experiences that fit students' individual needs. Second, limited resources such as diverse teaching materials and different assessment instruments pose a real challenge in providing effective responses to variations in student styles and levels of understanding. Third, it is difficult to ensure active involvement of students in the classroom mainly due to time constraints and students' skills that are still developing. Fourth, teachers' understanding and skills in applying differentiated learning are still lacking The barriers found in this study are real challenges faced by sociology teachers, and indicate the need for more intensive training and support to optimize differentiated approaches in the sociology learning process.